N-acetyl-L-leucine normalizes Transcription Factor EB activity by stereospecific bidirectional modulation in a HeLa cell model of Niemann-Pick disease type C - Lianne C. Davis; Wim Annaert; Rebecca Braine; Grant C. Churchill; Mallory Factor; Taylor Fields; Marc Patterson; Frances Platt; Dawn Shepherd; Michael Strupp; Antony Galione (PLoS ONE, 2026)
Levacetylleucine (Aqneursa™), an acetylated derivative and pro-drug of L-leucine, is the only FDA-approved monotherapy for Niemann–Pick disease type C (NPC). Its acetyl group enables transport via monocarboxylate transporters, supporting blood–brain barrier penetration and efficient cellular uptake. Inside cells, levacetylleucine is metabolised by acylases, generating elevated levels of L-leucine that enhance mitochondrial bioenergetics and is thought to ameliorate lysosomal dysfunction indirectly. Here, we describe a direct effect of levacetylleucine on lysosomal regulation through modulation of TFEB, the master transcription factor for lysosomal and autophagy genes. Levacetylleucine rapidly alters TFEB translocation between the cytoplasm and the nucleus in a biphasic, homeostasis-restoring manner. In wild-type HeLa cells, levacetylleucine promotes TFEB activation and nuclear localisation. However, in NPC1 disease models, where we show that TFEB is over-activated and enriched in the nucleus due to lysosomal stress, levacetylleucine reduces nuclear TFEB and restores a more normal cytoplasmic-to-nuclear balance. These effects occur at clinically relevant concentrations associated with lysosomal storage reduction. The effects of the drug are stereospecific: while the L-enantiomer is active, the D-enantiomer and racemate show no effect, revealing the antagonistic properties of the D-enantiomer. This bidirectional normalisation of TFEB activity highlights a direct mechanism through which levacetylleucine modulates lysosomal and autophagic pathways in the HeLa cell model, giving mechanistic insight into its therapeutic potential in NPC, and also across diverse neurological and neurodevelopmental disorders.